Incidence and outcome of patients with renal cell carcinoma treated with partial or radical nephrectomy in the Cantons St Gallen and Appenzell 2009–2018 (Swiss Medical Weekly, 2022)
BACKGROUND: Over recent years, the incidence of renal cell carcinoma (RCC) has remained unchanged in Switzerland and is low compared with other European countries. Partial or radical nephrectomy is the mainstay of treatment in patients with localised disease.METHODS: We conducted an analysis of data from the cancer registry of Eastern Switzerland on patients with surgery for RCC from 2009 to 2018, focusing on a comparison of surgical technique and outcome in tertiary and non-tertiary hospitals.RESULTS: 492 nephrectomies were performed. Out of 441 curative procedures, 226 were radical and 195 partial nephrectomies (20 unknown). At the tertiary hospital, statistically significantly more partial nephrectomies were performed in non-metastatic patients than at non-tertiary hospitals. We demonstrate a trend towards better disease-free survival after partial compared with radical nephrectomy. The 5-year overall survival for patients diagnosed between 2009 and 2013 was 85%, 83%, and 70% in stage I, II, and III, respectively, compared with 96%, 78%, and 72% for patients diagnosed between 2014 and 2018.CONCLUSION: RCC incidence in Switzerland has been stable during the past decade in contrast to other European countries, and no stage migration occurred. We demonstrated that patients with localised renal cancer at our tertiary centre were more likely to be treated with renal preserving surgery compared with non-tertiary hospitals. This analysis underlines the importance of local cancer registries in the comparison of treatment and outcome over time.